Molecular Characterization, Multiple Drug Resistance, and Virulence Determinants of Pseudomonas aeruginosa Isolated from Lebanon - Tokajian, Sima (2012)
Aims: Typing and characterization of 100 P. aeruginosa clinical isolates by pulse field gel electrophoresis (PFGE) to detect changes in the clonal composition of local strains and to correlate banding patterns with site of infection, drug resistance and Type III secretion system effectors. Methodology: A total of 100 P. aeruginosa isolates obtained from clinical specimens were used to study resistance profiles, PFGE banding patterns and virulence determinants. Results: Results from antimicrobial susceptibility testing yielded showed that 77 of the strains were multi drug resistant (MDR). Grouping isolates as non-susceptible when tested intermediate and resistant accordingly showed that resistance was 25% each for imipenem and piperacillin-tazobactam, while it was 29% for ceftazidime these drugs are among the ones most commonly used in treating infections caused by P. aeruginosa. Studying effectors released by the type III secretion system including exoU and exoS revealed that 48% of the isolates harbored exoS toxin gene and 46% the exoU, with 3% having both and 8% having none. When the different pulsotypes were compared on a dendogram, 45 Short Communication British Microbiology Research Journal, 2(4): 243-250, 2012 244 groups emerged showing vast differences among the isolates. Conclusion: This study showed the emergence of drug resistance in P. aeruginosa against the antimicrobial agents being routinely used for treatment and revealed the likely presence of co-selected traits that result in highly virulent and resistant strains. Further clinical investigations are warranted to combat infections caused by this important human pathogen in Lebanon.